EFFECT OF LACTOFERRIN ADDTION TO SEMEN OF AWASSI RAMS ON THE BACTERIAL CONTAMINATION - & Houbi, Mahdi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This study was conducted at the farm of Animal production, College of Agriculture, University of Baghdad, Algaderia to know the effect of lactoferrin protein addition in the semen extender of Awassi during the  period from 21 September 2015 to 24 February 2016 on Four Awasi rams aged 2-4 years and the average weight was 52 kg were used in this study . Semen collection from rams was done twice weekly by using the artificial vagina then it's were pooled and divided in to four treated groups, the control (normal antibiotic Streptomycin 100 mg\100ml Penicillin  100.000 IU / 100ml) , second ,third and fourth treated groups was used a lactoferrin  protein with the contamination of 400 , 800 and 1200 mg \ L-1, respectively .After dilution the semen samples have been kept at the refrigerator (5 C) for 5 days to measure some physical properties of sperm which included the acrosome integrity and some bacteriological examination (type and number) .Data obtained from this experiment showed that there was no significant difference (p≥0.05) in the acrosome integrity of sperm between the control and treated groups (2,3 and 4) which were decrease  the most types of bacteria in the semen samples , where as the type of bacteria in group 2 were sphingomonas and Stenotrophomonas  and in groups 3 and 4 were Klebsiella, Proteus, Cupriavidus, while there were six types of bacteria in the control group (Escherichia, Klebsiella, Staphylococcus, Salmonella, Enterobacter , and  Staphylococcus epidermidis ) . It was concluded that the use of lactoferrin in the semen causing adecrease in the total number of bacteria in the semen.